Diversity of palatal rugae patterns and their reliability in sex discrimination in a South Indian population - Sai Madhavi Nallamilli; Ramesh Tatapudi; Sudhakara Reddy Reddy; Sai Kiran Chennoju; Ramya Kotha; Pavani Kotha (Wolters Kluwer Medknow Publications, 2015)
Introduction and Aims: Array of palatal rugae in the realm of forensic odontology has been constantly explored owing to their individual uniqueness and resistance to postmortem procedures, while their scope in sex determination and racial profiling remains understated. In this context, the present study aimed to record the diversity of palatal rugae patterns in a South Indian population. Materials and Methods: A descriptive cross-sectional study was conducted among people who reported to the outpatient department of a dental institution. Sample comprised a total of 200 subjects divided into two groups of 100 each, based upon gender. Impressions of anterior maxilla were made of all the study subjects and casts obtained subsequently. Outline of palatal rugae pattern was traced on these models and the data computed. Z test and unpaired t-test were used for statistical analysis and the probability value calculated. In addition, logistic regression analysis was performed to estimate the accuracy of sex allocation. Results: The shape of rugae exhibited highly significant sex difference in the curved type, which was found to be higher in males, and in the wavy type which was higher in females, enabling sex differentiation using palatal rugae patterns. Logistic regression analysis predicted high power of sex allocation for males rather than females in the study population. Conclusion: This study highlighted the uniqueness and greater sex discrimination potential of curved shape of palatal rugae in categorizing males of South Indian population, substantiating their use in the identification of deceased, by relating the antemortem and postmortem dental records.